Implementation of Dijkstra Algorithm with React Native to Determine Covid-19 Distribution - Rosyid Ridlo Al Hakim; Purwono Purwono; Yanuar Zulardiansyah Arief; Agung Pangestu; Muhammad Haikal Satria; Eko Ariyanto (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2022)
Since Covid-19 was declared a global pandemic because it has spread throughout the world, every effort has been made to help prevent and tackle the transmission of Covid-19, including information technology. Information technology developed to determine the shortest distance for Covid-19 cases around us needs to be developed. This research implements Dijkstra's Algorithm written in the React Native programming language to build a Covid-19 tracking application. The system can display the closest distance with a radius of at least one meter, and the test results can map the nearest radius of 41 meters and the most immediate radius of 147 meters. This system is built for the compatibility of Android OS and iOS applications with React Native programming.